TRADISI BACAMIN BANGKAI DI JORONG PANTI NAGARI RAMBATAN PERSPEKTIF HUKUM ISLAM - Ramadan Eka Putra; Zulkifli Zulkifli (Institut Agama Islam Negeri Batusangkar, 2022)
The main problem in this study is what causes the tradition of bacamin carcasses in Jorong Panti Nagari Rambatan and how Islamic law views about this tradition. This type of research is field research (field research) that is descriptive with a qualitative approach, namely research that uses events and phenomena that occur in the field through interviews with Religious Figures, Niniak Mamak, Wali Nagari, and to the wife whose husband has died. The results of the study found that the cause of the tradition of bacamin carrion is not justified with certainty, because it has been in effect for a long time and the people of Jorong Panti have become accustomed to this habit. Every husband or sumando who died while the wife was still at productive age, the wife's family would return the body to her family to be buried in her family's burial ground. According to Islamic Law, public confidence in the spirit of the ex-husband will interfere with the wife's domestic relationship with her husband in the tradition of Bacamin Carrion is shirk. So it can be called Urf Fasid and contrary to Islamic Law because of the shirk element.